KEDUDUKAN PARATE EKSEKUSI HAK TANGGUNGAN SEBAGAI ALTERNATIF PENYELESAIAN KREDIT MACET DIPERBANKAN - I DEWA AGUNG AYU MAS PUSPITANINGRAT; I Made Artha Rimbawa; I Wayan Putu Sucana Aryana; Putu Chandra Kinandana Kayuan (Fakultas Hukum Universitas Ngurah Rai, 2025)
Given the importance of the position of funds in credit in the development process, it is appropriate that creditors and credit recipients as well as other related parties receive legal protection through a rights institution. a strong guarantee and can also provide legal certainty for all parties. This study describes the parate execution process as an effort to resolve bad loans with mortgage guarantees, as well as the weaknesses and strengths of the parate execution efforts. The research method used in this study is a normative legal research method that is prescription. This study uses secondary legal materials which include primary legal sources and secondary legal sources. The approach used is the legal approach and the historical approach. Data Collection techniques used document study techniques with interpretation data analysis methods. The results showed that the process of parate execution of mortgages as an effort to settle bad loans was carried out based on law number 4 of 1996 concerning Mortgage as an effort to settle bad loans with guarantees of mortgages carried out under civil procedural law. The resolution of bad credit problems with mortgage guarantees, parate execution is considered faster and cheaper than civil lawsuits. In the parate execution process, there are obstacles in emptying the house, if the auction proceeds are less than the debtor’s debt, and if there are lawsuits and resistance. However, with the parate of execution, it provides legal certainty and the creditor’s position will be more protected if the debtor breaks his promise, because the debtor seems to have set aside part or all of his material assets to pay off his debts in the future.